PENERAPAN METODE DEMPSTER SHAFER PADA SISTEM PAKAR DIAGNOSA AWAL HAMA DAN PENYAKIT TANAMAN KARET BERBASIS WEB (STUDI KASUS DI DESA TANJUNG PAUH TALANG PELITA JAMBI) - Kahar, Novhirtamely; ., Sentia (FORTECH (Journal of Information Technology), 2019)
Indonesia is one of the largest producers and exporters of natural rubber in the world. Every year rubber production in Indonesia shows an improved prognosis. Most rubber producers in Indonesia come from the provinces of South Sumatra, North Sumatra, Riau, Jambi and West Kalimantan. The Jambi Provincial Plantation Office has always tried to maintain the quality of rubber plants in order to remain productive. One of the efforts is to help rubber farmers in caring for rubber plants to keep producing high-quality rubber latex. This study aims to build an expert system software application for early diagnosis of rubber plant diseases using the web-based Dempster Shafer method. With this application it is expected to help rubber farmers get information about rubber plant care and provide solutions to rubber plants that are experiencing disturbances. This application was built with php connected to the MySql database. Inputs in this application are data on symptoms, pests and diseases, users, rules, and consultation history. In this system uses a calculation process with the Dempster Shafer method, which calculates the weight of each symptom, compares the weight of each symptom, and determines the percentage of disease belief based on the selected symptoms. The output of this expert system application is information about pests in rubber plant diseases, and reports on the results of early diagnoses of rubber plant diseases. The results of this study indicate that the type of rubber plant disease that is often experienced by rubber plantations in the village of Tanjung Pauh Talang Pelita Jambi during January-May 2019 is White Root Fungus caused by the fungus Rigidoporus Lignosus or R. Micropus. With the application of an expert system using the dempster shafer method, it can help rubber farmers deal quickly with pests and diseases that attack rubber plants, so as to reduce the risk of sudden death on rubber plants.